PROFILE OF HISTORY OF FEBRILE SEIZURE IN PATIENTS WITH EPILEPSY - Basyarahil, Rayhan Muhammad; Islamiyah, Wardah Rahmatul; Gunawan, Prastiya Indra (MNJ (Malang Neurology Journal), 2022)
Background: Febrile seizure is convulsions with fever (temperature ³38°C) with no central nervous system infection that commonly found in children (6-60 months). Febrile seizures do not always mean the child has epilepsy. However, febrile seizures can be a possible long-term risk factor for epilepsy.Objective: The objective of this study is to know the profile of febrile seizure in patients with epilepsy.Methods: A retrospective descriptive study on 23 patients with epilepsy in the EEG Department of Neurology, Dr. Soetomo General Hospital, Surabaya, Indonesia in the period 2018-2019 based on inclusion and exclusion criteria. The total number of epilepsy patients is 849 patients, 216 of whom had a history of febrile seizure. Among 216 epilepsy patients who had a history of febrile seizures, 23 of them were qualified as the sample. The sampling technique used was total population sampling. The instrument of this research is the patients’ medical record. Data analysis is carried out descriptively.Results: The characteristics of the history of febrile seizures that found in patients with epilepsy are more patients are male, have the age of onset on less than 2 years old, have the body temperature more than 38.3°C, have the seizure duration less than 15 minutes, have focal seizures, have recurrent seizures in 24 hours, have a history of more than one febrile seizure, have accompanying neurological disorders, and have no family history of epilepsy.Conclusion: Febrile seizure is still becoming a concern because there is a possibility that it may develop into epilepsy. Even though, not all children who experience febrile seizure will generate epilepsy.